Science learning with ecotourism insight at the Benang Stokel Waterfall, Batukliang Utara - Evi Eli Dayani; Agil Al-Idrus; Rosy Dwi Selvi; Muhammad Hanafi (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2023)
This study aims to determine science learning with ecotourism insight at the North Batuliang Stokel waterfall. The method used in this journal is a descriptive qualitative method with data analysis through interviews and observation with the aim of describing science learning at the Thread Stokel Waterfall tourist spot. The learning material is material about energy in life in class VII SMP. The object in science learning is a waterfall of Benang Stokel which is an example of energy in everyday life.